Correcting the principle of two-level litigation in the Algerian Administrative Judiciary by establishing administrative courts of appeal under law 22/13 - Hairech, Noureddine; Djeriou, Mohammed Elamine; Derbale, Mohammed (The International tax journal, 2025)
This article aims to explain and clarify the administrative judicial organization in Algeria before the year 2022, which was proceeding in a way that contradicted one of the principles of the Algerian judiciary, especially the principle of two-level litigation, which was not applied correctly during that period, and what the administrative judicial organization became in Algeria after the amendment of the Civil and Administrative Procedures Law, Law 08/09, according to Law 22/13 Which established the principle of two-level litigation in this field in a manner befitting the reputation of this judicial field, especially after the Algerian legislator redistributed the powers and tasks among the various judicial authorities in its new form, especially after the creation of administrative courts of appeal, through study, extrapolation, and analysis of various legal texts Related to this area, let us finally conclude that the Algerian legislator did well with this amendment, which corrected a mistake that had been in effect for 28 years in the failure to properly apply the principle of two-level litigation in the Algerian administrative judiciary.